TULP3 Regulates Proliferation and Differentiation of 3T3-L1 Preadipocytes Through the Hedgehog Signaling Pathway - Xinlin Jin; Yu Zhang; Yunzhou Wang; Hongzhen Cao; Qi Song; Jingsen Huang; Wei Chen; Hui Tang; Yongqing Zeng (Biology)
The TULP family was first identified in progressively obese mice, and TULP3, as a member of its family, has been much studied in tumor cells, but studies on its role in adipocytes have not yet been reported. This study found that the expression of TULP3 showed an increasing trend in the differentiation of 3T3-L1 cells, and overexpression of TULP3 enhanced the proliferation and differentiation capacity of the cells, while inhibition caused the opposite result. TULP3 is a negative regulator of the Hedgehog signaling pathway, which can control lipid metabolism in adipose tissues, but whether TULP3 can play a role in adipose tissues through the Hedgehog signaling pathway is not yet known. It was experimentally found that TULP3 could promote adipogenic differentiation of precursor adipocytes by inhibiting the activity of the Hedgehog signaling pathway. Our results elucidate the role of TULP3 in the generation of precursor adipocytes and provide useful information for a deeper understanding of the molecular mechanisms of adipocytogenesis, which will contribute to the improvement of the treatment of adipose tissue dysfunction or uncontrolled adipogenesis-related diseases.